Entry System in Matrix Form and Computerized System (Al-Mansour Journal, 2022)
It can easily be seen that the Science of Accounting now closely adheres itself to the economic and technological developments as well as the revolution of information and continuous progress in business environment, scientifically investing them to promote the professionalism of accounting, and to guarantee business services and its planning and monitoring functions and, ultimately, to participate in decision-making efficiently and actively. The aim is to promote the economic value and its intellectual capital by virtue of the dependence of accounting on the criteria of scientific principles, objectivity, reliability and validity.Significantly, it is observable that the scientific and pragmatic frame of accounting has kept the flow of accounting and financial information through securing accounting systems relevant to the registering of the financial deals of economic units. The systems are to adjust and report them for the benefit of both internal and external sides. Book keeping, whether manual or technical or whether single entry or single and double entry or double entry be applied, is an important component in accounting course. The latter entry has been made obligatory as being officially approved by the laws and instructions of States and professional organizations.Entry system in matrix form is seen by researchers an advanced connecting link to that preceding it, being invested by accounting sciences through employing mathematics (matrices) and its elements and through having single entry and doubleresults to feed computer systems (Foxpro) and complete the accounting cycle. The ultimate aim is to affirm financial deals and to find out the outcome of the work and financial reports, things that are the objectives of this paper.
Keywords: القید المفرد; القید المزدوج; الدورة المحاسبیة; القید بالمصفوفة